Ethni-City : Educational Game Development about History of the Multicultural City of Surosowan as an Effort to Integrate Diversity - Nuhiyah, Nuhiyah; Febriyanti, Lia; Alwiyah, Siti (Yupa: Historical Studies Journal, 2024)
This research aims to develop Ethni-City game, a contemporary innovation to promote diversity in Banten Province by exploring the historical context of the Multicultural City of Surosowan. The research methodology involves historical research and the research and development (R&D) method using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The outcome of this study is the development of the Ethni-City game, a digital educational tool highlighting the history and culture of five villages within the Multicultural City of Surosowan: Bugis Village, Pekojan Village, Chinatown, European Village, and Kebalen Village. The game underwent expert evaluation, resulting in a rating of 'Highly Feasible/Excellent.' Implementation of the game received positive responses from respondents, who viewed it as an engaging educational medium for introducing diversity to the people of Banten Province.